(untitled) (Impact: Journal of Transformation, 2026)
The phrase in persona Christi - “in the person of Christ” - expresses one of the deepest mysteries of Christian ministry: that in sacramental actions, it is Christ Himself who ministers through the Church’s ordained servants. This paper explores the application of this doctrine within the Anglican Church, with a particular focus on the Kenyan context. It argues that Anglican theology, shaped by the Reformation’s via media, holds a distinctive balance between sacramental objectivity and communal participation. The priest, acting in persona Christi, is neither a mystical intermediary nor a mere functionary, but a representative servant through whom Christ’s reconciling grace flows to the faithful. Historically, the concept emerged from Catholic teaching affirmed by the Council of Trent, was critiqued and reinterpreted by the Reformers, and found renewed expression in Anglicanism’s synthesis of Scripture, tradition, and reason. In Kenya, the doctrine is not abstract but embodied in pastoral realities; single mothers seeking acceptance, elderly polygamists walking paths of conversion, and believers living with HIV longing for healing at the Eucharistic table. Acting in persona Christi thus calls clergy to embody Christ’s hospitality, truth, and mercy amid cultural diversity and moral complexity. The study concludes that this doctrine anchors the Church’s sacramental life in Christ’s faithfulness, nurtures communal priesthood, and inspires servant leadership rooted in the Gospel’s call to reconciliation.